The Weibull Regression Model Analysis of Mahakam River Water Pollution Potential - Pradipa, Zalva; Suyitno, Suyitno; Siringoringo, Meiliyani (Universitas Bumigora, 2024)
Mahakam River has a vital role in the lives of the people of the East Kalimantan province, includingproviding a raw source of clean water. The multi-activity of the Mahakam River watershed, as a watertraffic lane, mining, fisheries, hotels, restaurants, and resident houses, has the potential to produce wasteinto the water. Increasing waste in the water flow can increase the pollution potential of river water,threatening people’s health. Therefore, precaution is necessary. In this research, statistical preventionwas proposed, providing information to the East Kalimantan people regarding the factors affecting thepollution potential of the Mahakam River through Weibull regression (WR) modeling on dissolved oxygen (DO) data 2022. Research data was secondary data provided by the Life Environmental Departmentof East Kalimantan province. The WR model is a Weibull distribution that is directly influenced by covariates. WR model consists of Weibull survival regression, cumulative distribution regression, hazardregression, and Weibull mean regression. This research aims to obtain the factors affecting the pollution potential and to provide the pollution potential information of Mahakam River 2022. The researchconcluded that factors influencing the pollution potential of the Mahakam River were watercolor degreeand nitrate concentration. Applying the WR model to DO data 2022 was able to provide the pollutionpotential information of Mahakam River, namely the probability of river water isn’t polluted is 0.6555,or the probability of the polluted river water is 0.3445, the pollution rate is 6 locations are polluted forevery 10 mg/L DO, and the DO average of river water is 5.7450 mg/L. Increasing water color degreeand nitrate concentration will decrease the probability of the Mahakam River being polluted, increasethe probability of the Mahakam River being polluted, increase the pollution rate, and reduce the DO ofMahakam River water.